2012
DOI: 10.1021/cr3000219
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Electrons with Bare and Hydrated Biomolecules: From Nucleic Acid Bases to DNA Segments

Abstract: 5607 2.4. Polarizable Continuum Model 5608 3. Electron Attachment to Nucleic Acid Bases and the DNA Backbone 5608 3.1. Guanine 5608 3.2. Adenine 5609 3.3. Cytosine 5609 3.4. Thymine and Uracil 5610 3.5. 5-Halouracils 5610 3.6. DNA Backbone 5611 3.7. Hydrogen Abstracted Nucleobases 5611 4. Electron Attachment to Microsolvated Bases 5612 4.1. Adenine-(H 2 O) n 5612 4.2. Cytosine-(H 2 O) n 5612 4.3. Thymine-(H 2 O) n 5612 4.4. Uracil-(H 2 O) n 5612 4.5. H-Bonded Nucleic Acid Bases 5612 5. Electron Attachment to N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
234
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(245 citation statements)
references
References 242 publications
7
234
1
3
Order By: Relevance
“…The results presented in Ref. [1] motivated a large amount of both experimental [11,30,31,32,33] and theoretical [34,35,36] work that aimed at elucidating the role played by LEE in DNA damage. In recent years, this research has moved on from idealized systems, e.g.…”
Section: Radiation Damage Of Dnamentioning
confidence: 94%
See 1 more Smart Citation
“…The results presented in Ref. [1] motivated a large amount of both experimental [11,30,31,32,33] and theoretical [34,35,36] work that aimed at elucidating the role played by LEE in DNA damage. In recent years, this research has moved on from idealized systems, e.g.…”
Section: Radiation Damage Of Dnamentioning
confidence: 94%
“…The BLYP affinity is fortuitously close to the PS experimental value. [36] Experimental Reference PS 0.15 ± 0.12 [117] More accurate functionals are constructed by combining GGAs with HF (exact) exchange in an appropriate proportion. This is the case for the hybrid B3LYP functional [124,125], which has proved itself to be particularly reliable for predicting AEAs of DNA components [122].…”
Section: Electron Affinitiesmentioning
confidence: 99%
“…Theoretical simulations of electron scattering and electron capture via "shape" resonances support the role of LEEs in DNA strand breaks [94]. Theoretical calculations on scattering and attachment of LEEs to DNA components up to supercoiled plasmid DNA have been intensively reviewed in recent years [95,96].…”
Section: Electron Attachment To Short Single-stranded and Plasmid Dnamentioning
confidence: 99%
“…2 Transient anion states of nucleobases have been posited to play a major role in DNA mutagenesis, perhaps via a charge-transfer process from an initially charged nucleobase moiety to a sugar-phosphate bond. 3,4 In this work, we explore the dynamics of transient anion states of uracil via time-resolved photoelectron (TRPE) imaging 5 of an iodide-uracil binary complex.The interaction of excess electrons with uracil and other nucleobases has been studied in the gas phase using low-energy electron scattering, 6,7 negative ion photoelectron spectroscopy (PES), 8−10 and Rydberg electron transfer (RET). 11 Total electron scattering cross section measurements showed structure below 2 eV associated with unoccupied π* orbitals of uracil, 6 while dissociative electron attachment (DEA) studies showed that hydrogen atom loss from the N1 position in the transient negative ion U* − occurs at collision energies as low as 0.7 eV.…”
mentioning
confidence: 99%